Legal Protection Of Patients Subjected To Medical Refusal In Health And Human Rights - Irfan; aulia, happy amanda; Permatasari , Galuh (Universitas Duta Bangsa Surakarta, 2023)
Human rights are rights bestowed by God Almighty to every individual on earth. Everyone is obliged to protect and respect the rights of everyone. Human rights are legal and normative concepts which state that humans have inherent rights because they are human beings. Human rights apply anytime, anywhere, and to anyone so that they are universal. Human rights include the right to a healthy life and work, the right to get health services, and special attention, everyone has the right to a healthy life. sufficient for the health and well-being of himself and his family. As a result of violations of human rights (HAM) in the field of health services, it can cause losses to people who really need the fulfillment of adequate health services, so that law enforcement efforts are needed against perpetrators of violations in health services for the community. This is intended to provide guarantee protection for the community related to violations of the right to health. In the health sector, acts of human rights violations can involve heads of health service facilities or health workers who carry out practices or work in health care facilities that are contrary to the health law. The research aims to determine the consequences of violations of human rights in health services, so that the fulfillment of the right to health is not achieved and law enforcement against violations in health services is viewed from the aspect of human rights and the specific objective is to find out the laws and regulations governing the right to obtain health services and enforcement of violations in health services.